Strategic Planning for IS/IT Using Ward and Peppard at Maman Elektronik Sokaraja - Michelle, Olivia; Fritz Wijaya, Agustinus (Universitas Nusantara PGRI Kediri, 2020)
Maman Elektronik Sokaraja has implemented SI / IT, but it is not evenly distributed in all fields. The uneven implementation of the business process is still not effective and efficient. The purpose of this research is to provide an IS / IT strategic plan so that it can assist in the implementation of the company's IS / IT so that it is more equitable. The method used in this research is the Ward and Peppard method which consists of a SWOT analysis, Value Chain, Five Force Model, McFarlan Strategic Grid. The results of the study that have been carried out have obtained a recommendation for the development of several applications such as SI Sale, SI Debt and Receivable, SI Purchase and SI Inventory. Some of the recommended apps, such as SI Sales Distributor, SI Accounting, SI Payroll, SI Attendance. The application is approved in stages over 4 (four) years according to company conditions. Developments in several SIs required several application plans to be implemented within four years.